2023
DOI: 10.3389/fphys.2023.1088813
|View full text |Cite
|
Sign up to set email alerts
|

Predictive utility of commercial grade technologies for assessing musculoskeletal injury risk in US Marine Corps Officer candidates

Abstract: Recently, commercial grade technologies have provided black box algorithms potentially relating to musculoskeletal injury (MSKI) risk and functional movement deficits, in which may add value to a high-performance model. Thus, the purpose of this manuscript was to evaluate composite and component scores from commercial grade technologies associations to MSKI risk in Marine Officer Candidates. 689 candidates (Male candidates = 566, Female candidates = 123) performed counter movement jumps on SPARTA™ force plates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, according to SS, their RSI is calculated as jump height divided by contraction time (or time to take off) with units reported as meters per second. Yet, at this time, SS referred to this metric as RSI which is typically calculated as the ratio of flight time to contraction time and others have identified this calculation from SS as jump height divided by time to peak force (2). Thus, we recalculated mRSI as jump height divided by time to take off, and the comparisons of SS to FD (CCC 5 0.71, MAPE 5 22.93) and HD (CCC 5 0.85, MAPE 5 28.82) were improved but still resulted in systematic and proportionate bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, according to SS, their RSI is calculated as jump height divided by contraction time (or time to take off) with units reported as meters per second. Yet, at this time, SS referred to this metric as RSI which is typically calculated as the ratio of flight time to contraction time and others have identified this calculation from SS as jump height divided by time to peak force (2). Thus, we recalculated mRSI as jump height divided by time to take off, and the comparisons of SS to FD (CCC 5 0.71, MAPE 5 22.93) and HD (CCC 5 0.85, MAPE 5 28.82) were improved but still resulted in systematic and proportionate bias.…”
Section: Discussionmentioning
confidence: 99%
“…Coefficients of variation (CoV) and intraclass correlation coefficients of single measures and random testers (ICC [2,1]) were used to test within-session reliability (individual trials within a single CMJ session). Based on previous reports of similar biomechanical metrics, the threshold for acceptable variation was set to CoV ,10% (7,26).…”
Section: Kinetic Data Analysismentioning
confidence: 99%
“…However, force-time data have been used to provide additional, valid, and reliable metrics pertaining to vertical countermovement jump (CMJ) movement and performance (5,(18)(19)(20). Although CMJ assessment is primarily aimed to monitor athlete fatigue or training progressions, recent interest pertains to associations with injury risk in tactical and sport athletes (6,7,12,22).…”
Section: Introductionmentioning
confidence: 99%
“…Others have found no difference in eccentric rate of force development between injured and noninjured athletes, but a greater ratio of eccentric rate of force development to average concentric mean force existed for the injured group compared with noninjured group (24). Much of this research has occurred in military settings, which has shown mixed results regarding baseline jump assessments, on force plates being associated with musculoskeletal injury risk (MSKI) during training (6,7,14). Nonetheless, movement screening associations with MSKI are complex, and discrepancies are likely due to variations in previous injury, sex, sport, competition level, and training requirements (1,11,16,26).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the injuries were not classified as contact or non-contact injuries, which makes interpretation of the data challenging [ 17 ]. Still in their infancy, other works in the existing literature within the field of health and sport have used markerless motion capture systems to gain insights into human health and movement characteristics [ 10 , 18 , 19 , 20 ]. While the previously highlighted literature suggests the potentially effective use of markerless motion capture technologies, particularly from a validity standpoint, certain degrees of uncertainty pertaining to the reliability of such devices still remain, especially across a wide range of movement tasks and variables.…”
Section: Introductionmentioning
confidence: 99%